2022
DOI: 10.1001/jamanetworkopen.2022.22385
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Rental Assistance Programs and Hemoglobin A1c Levels Among US Adults

Abstract: IMPORTANCE Programs that provide affordable and stable housing, such as federal rental assistance, may be associated with improved mean blood glucose levels and related diabetes outcomes.OBJECTIVE To assess whether 2 different types of federal rental assistance programs are associated with glycated hemoglobin A 1c (HbA 1c ) levels among middle-aged and older US adults. DESIGN, SETTING, AND PARTICIPANTSThis cohort study used data from the National Health and Nutrition Examination Survey (NHANES) linked with US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A study using the National Health and Nutrition Examination Survey (NHANES) survey data from 1999–2016 comparing 795 adults receiving either project-based housing ( n = 450) or housing vouchers ( n = 345) to 255 adults not yet receiving assistance but remained on the waitlist, found that those receiving project-based housing had lower HbA1c levels compared to the waitlist group, but the differences were not statistically significant. The authors did find, however, that residence in project-based housing was associated with a lower prevalence (− 3.7%, 95% CI − 7.0, 0.0%) of uncontrolled diabetes, defined as HbA1c ≥ 9.0% (74.9 mmol/mol), compared to the waitlist group [ 61 ]. A longitudinal cohort study by Lim et al found that residence in New York City public housing was associated with higher prevalence of stable housing pattern (PR 1.16, 95% CI 1.07, 1.25), based on number of address changes over the 12-year follow-up period, but not with reduced diabetes risk (relative risk [RR] 1.11, 95% CI 0.83, 1.48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study using the National Health and Nutrition Examination Survey (NHANES) survey data from 1999–2016 comparing 795 adults receiving either project-based housing ( n = 450) or housing vouchers ( n = 345) to 255 adults not yet receiving assistance but remained on the waitlist, found that those receiving project-based housing had lower HbA1c levels compared to the waitlist group, but the differences were not statistically significant. The authors did find, however, that residence in project-based housing was associated with a lower prevalence (− 3.7%, 95% CI − 7.0, 0.0%) of uncontrolled diabetes, defined as HbA1c ≥ 9.0% (74.9 mmol/mol), compared to the waitlist group [ 61 ]. A longitudinal cohort study by Lim et al found that residence in New York City public housing was associated with higher prevalence of stable housing pattern (PR 1.16, 95% CI 1.07, 1.25), based on number of address changes over the 12-year follow-up period, but not with reduced diabetes risk (relative risk [RR] 1.11, 95% CI 0.83, 1.48).…”
Section: Resultsmentioning
confidence: 99%
“…8 vouchers CVD CVD-related outcomes: history of heart attack or stroke (self-reported), hypertension Lower odds of CVD-related outcomes in unassisted housing group (OR 0.394, 95% CI 0.204, 0.761, p ≤ 0.01) and housing voucher group (OR 0.527, 95% CI 0.280, 0.992, p ≤ 0.05) compared to public housing group Chambers et al 2021 [ 59 ] Cross-sectional Bronx, New York 5846 adults with type 2 diabetes receiving care at Bronx, New York-based hospital system Social needs: housing quality, housing instability (worry about eviction/ homelessness), food insecurity, health transportation, cost-related healthcare nonadherence, utility insecurity, conflicts with family, child or elderly care needs, legal needs, and intimate partner violence Diabetes Diabetes control (HbA1c) Presence of ≥ 3 social needs associated with higher likelihood of uncontrolled diabetes defined as HbA1c ≥ 9.0% (74.9 mmol/mol, adjusted OR 1.59, 95% CI 1.26, 2.00. Presence of housing issues (including needs related to housing quality and instability) associated with higher likelihood of uncontrolled diabetes ( p < 0.05) Charkhchi et al 2018 [ 60 ] Cross-sectional Nationwide survey (BRFSS) 84,353 US adults Housing insecurity: worry about paying rent/mortgage CVD CVD: myocardial infarction, angina, coronary heart disease (self-reported) CVD associated with increased odds of housing insecurity (OR 1.69, 95% CI 1.07, 2.66) Fenelon et al 2022 [ 61 ] Cohort Nationally representative survey (NHANES) 1050 adults receiving rental assistance or on a waitlist at time of NHANES survey Rental assistance: project-based housing, housing vouchers Diabetes HbA1c Project-based housing associated with decreased prevalence of HbA1c ≥ 9.0% (74.9 mmol/mol; prevalence − 3.7%, 95% CI − 7.0, 0.0%) compared to waitlist (prevalence 6.9%); no significant differences in HbA1c between voucher and waitlist groups Fertig & Reingold, 2007 [ 62 ] Cohort Nationally representative survey (FFCWS) 3 subsamples: 1) 422 mothers living in public housing at baseline vs. 2055 in comparison group; 2) 323 mothers who moved into public housing between baseline and year 1 vs. 199...…”
Section: Methodsmentioning
confidence: 99%
“…This pseudo-waitlist approach has been used in prior studies to assess HUD housing assistance. 35 38 , 50 , 51 In addition, we selected a 2-y waiting list duration to reflect the national average wait time for HUD housing assistance at the time of our analysis. 32 Sensitivity analyses conducted in prior studies confirmed that over 70% of adults in the pseudo-waitlist group were on the actual waiting list and had sociodemographic characteristics similar to those on the actual waiting list.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics published by HUD underscore that adults receiving HUD assistance have a high prevalence of chronic disease (18). However, analyses that use nationally representative data to assess associations between receiving housing assistance and the prevalence of chronic health conditions have been limited to specific populations (19,20) or self-reported outcomes of overall health status (7), physical activity (21), unmet medical need (5), or comparison groups not representing HUD-assistance-eligible people (22). Understanding the relationship between housing assistance and obesity, diabetes, and hypertension is important because these conditions disproportionately affect people who are at greater risk for housing insecurity, including people with low income (especially women) (23), people from racial and ethnic minority groups, and people with disabilities (13,16,17).…”
Section: Introductionmentioning
confidence: 99%